The Factors Affecting the Gender Equality in Iraqi Football Setting - Vajiheh Javani; Yasir Abdulrazzaq Fakhri Alyasiri; Fatemeh Abdavi (Shahid Bahonar University of Kerman, 2023)
This research aims to study the factors affecting gender equality in Iraqi football setting. The current research is based on a quantitative approach. The research population consisted of the employees of the football federation, players, and football coaches in Iraq. Based on Morgan's table, 384 people completed a researcher-developed questionnaire through random sampling. The content validity of the questionnaire was confirmed by eight professors of sports management. Convergent and divergent validity and composite reliability were checked and confirmed by the PLS software. Findings showed patriarchal culture, gender stereotypes, the variable of gender inequality in broadcasts, the biased performance of social media in gender equality, gender inequality in budgeting and financial support, the variable of public support for men's football, and inequality in accessing to sports facilities and equipment have significant effects on gender equality in Iraqi football setting. However, the findings reveal that family restrictions do not have significant effect on gender equality in Iraqi football setting.